The Influence of Developing an E-Business Adoption Model in Technological and Organizational Contexts in SMEs with TAM model: A Pretest Assessment - Asrul, Sani; Dian, Ikha P; Reida, Rachmawati; Ninuk, Wiliani; Indra, Samsie (2021)
Performance studies for SMEs (Small and Medium Enterprises) are feasible and can be done and used for a range of SMEs. One approach is to integrate and integrate Technology Acceptance Model and e-business conceptual framework are two instances of existing models to create a new model (TAM). This is a quantitative study using the Sequential Equation Model of the analyst (SEM). Before proceeding to the next phase of the process research, this study will establish the questionnaire's psychometric features and test it research. The tests are being performed to evaluate the level of validity and trust of the indicators used A 5 Likert rating scale is used in the questionnaire. The created path's effect is made of 12 connections and results in seven variables.